BOOK REVIEW: VICTOR COJOCARU, ANNAMÁRIA-IZABELLA PÁZSINT (EDS.), MIGRATION AND IDENTITY IN EURASIA: FROM ANCIENT TIMES TO THE MIDDLE AGES, CLUJ-NAPOCA: MEGA PUBLISHING HOUSE, 2021. - CIUBOTARU, Nica (Studia Universitatis Babeș-Bolyai Historia, 2023)
The collective volume reviewed below comprises twelve articles that revolve around the concepts of migration and identity. Most of the papers have been presented at the international conference entitled Migrations and Identity in European History: Communities, Connections, Conflicts, held in 2019 within the framework of a larger research project coordinated by the Romanian Academy branch from Iaşi. The conference had three panels, the presentations being grouped thematically and ordered chronologically. Thus, this book comprises studies connected to the subject of the first panel, which makes it the inaugural volume of a tripartite series. Let's start from the beginning: the Preface (p. 7-12). The editors commence by enumerating the various recent directions chosen by researchers when approaching the topical concepts of migration and identity from Antiquity to the Middle Ages. The terms and concepts are not defined, a discussion on the relevance of these directions is not proposed, an overview of these approaches is not given. The reader is simply being redirected towards the appropriate bibliography, a choice blamed by the editors on the requested space limits. As such, the book lacks an appropriate introduction.